Introduction to Entrepreneurship Based on Ethnopedagogy in the Ngetau Tradition for Elementary School Students - Suprapto, Hugo Aries; Widiyarto, Sigit; Rizkiyah, Nur; Nurisman, Husain; Megayanti, Windi; Vernia, Dellia Mila; Sumadyo , Bambang; Saring, S (Studies in Learning and Teaching, 2024)
The purpose of this study was to explore the enhancement of cultural education and entrepreneurial values among elementary school students through an ethnopedagogical approach in Ensaid Village, West Kalimantan. Cultural education for elementary school students remained suboptimal, resulting in many students being unaware of their traditions and culture. The independent curriculum had mandated cultural education through projects aimed at strengthening the profile of Pancasila students (P5), focusing on themes such as independence.. This research utilized a qualitative method with an ethnographic approach, involving respondents including teachers, community members, and tradition activists. All the respondent lived in Ensaid Village West Borneo Kalimantan. The research instruments consist of validated questionnaires created by experts, along with data collection methods that include observation, documentation, and interviews. Data analysis is conducted concurrently with data collection, employing domain analysis. This involves reviewing the data obtained from observations, interviews, and descriptive notes to validate the findings. Female was 5, and Male was 7. The process of entrepreneurial education could occur both in schools and at home with parents, through both formal and non-formal learning activities. An ethnopedagogical approach served to introduce cultural values that reinforce entrepreneurial learning in schools. One cultural asset that could be utilized was the Ngetau tradition, which teaches students important entrepreneurial values such as hard work, patience, resilience, and diligence.